Infants' indoor and outdoor residential exposure to benzene and respiratory health in a Spanish cohort. (March 2017) - Ferrero, Amparo; Esplugues, Ana; Estarlich, Marisa; Llop, Sabrina; Cases, Amparo; Mantilla, Enrique; Ballester, Ferran; Iñiguez, Carmen
Abstract: Benzene exposure represents a potential risk for children's health. Apart from being a known carcinogen for humans (group 1 according to IARC), there is scientific evidence suggesting a relationship between benzene exposure and respiratory problems in children. But results are still inconclusive and inconsistent. This study aims to assess the determinants of exposure to indoor and outdoor residential benzene levels and its relationship with respiratory health in infants. Participants were 1-year-old infants (N = 352) from the INMA cohort from Valencia (Spain). Residential benzene exposure levels were measured inside and outside dwellings by means of passive samplers in a 15-day campaign. Persistent cough, low respiratory tract infections and wheezing during the first year of life, and covariates (dwelling traits, lifestyle factors and sociodemographic data) were obtained from parental questionnaires. Multiple Tobit regression and logistic regression models were performed to assess factors associated to residential exposure levels and health associations, respectively. Indoor levels were higher than outdoor ones (1.46 and 0.77 μg/m 3, respectively; p < 0.01). A considerable percentage of dwellings, 42% and 21% indoors and outdoors respectively, surpassed the WHO guideline of 1.7 μg/m 3 derived from a lifetime risk of leukemia above 1/100 000. Monitoring season, maternal country of birth and parental tobacco consumption were associated with residential benzene exposure (indoor and outdoors). Additionally, indoor levels were associated with mother's age and type of heating, and outdoor levels were linked with zone of residence and distance from industrial areas. After adjustment for confounding factors, no significant associations were found between residential benzene exposure levels and respiratory health in infants. Hence, our study did not support the hypothesis for the benzene exposure effect on respiratory health in children. Even so, it highlights a public health concern related to the personal exposure levels, since a considerable number of children surpassed the abovementioned WHO guideline for benzene exposure. Graphical abstract: Highlights: Benzene exposure was measured inside and outside infants' dwellings using passive samplers. Both exposures were related mainly to sociodemographic traits and parental smoking. The WHO guidelines for benzene were surpassed in 42% and 21% indoors and outdoors, respectively. Neither indoor nor outdoor exposure was related to respiratory health in infants. A public health concern related to residential benzene exposure levels was identified. Abstract : Residential exposure to benzene, both indoors and outdoors, was not related to respiratory health in the first year of life; notwithstanding, a considerable percentage of dwellings, particularly indoors, surpassed the WHO guidelines.